Dioctophyme renale Goeze, 1782 in a cat with a supernumerary kidney - Pedrassani,Daniela (2014)
This study reports a case of parasitism by Dioctophyme renale in a supernumerary kidney and abdominal cavity of a female cat in Brazil. The three-year-old cat of indeterminate breed presented abdominal distension and was taken to the University of Contestado Veterinary Hospital in Canoinhas, state of Santa Catarina, since the owner suspected pregnancy. An ultrasound scan did not confirm pregnancy but revealed parasitism in the kidney. This case is worth reporting because domestic cats are rarely hosts of this nematode species.